Design and Development of a Power-Free Smart Cooler Box Using Phase Change Materials (PCMs) for Last-Mile Cold Chain Logistics - Helvina Aulia Zahra; Ahmad Rusdiansyah; Ratna Sari Dewi; Rindi Kusumawardani; Azzah Dyah Pramata; Fadila Isnaini (Institute of Research and Community Outreach - Petra Christian University, 2026)
The growing demand for fresh products requires efficient and sustainable cold chain logistics, especially in last-mile delivery. Conventional refrigerated trucks utilized in last-mile logistics are hindered by high energy consumption, operational costs, and limited flexibility, creating a critical barrier for small-scale cold chain access. To address these inefficiencies, this research develops a Power-Free Smart Cooler Box that integrates Phase Change Material (PCM) technology with a high-performance composite structure to maintain frozen-grade temperatures without active power. The design methodology employed the Theory of Inventive Problem Solving (TRIZ) to systematically resolve the engineering contradiction between maximizing thermal endurance and minimizing system weight. The resulting configuration features a multi-layer insulation wall (Fiberglass/Vacuum Insulated Panel/Polyurethane) and a validated 6-sided PCM layout. This configuration enables the Smart Cooler Box to maintain an internal air temperature of ≤ −10 °C for more than 10 hours without external power. It is also equipped with a built-in IoT-based temperature sensor to ensure real-time traceability. These findings imply that the developed passive cooler provides a scientifically validated, zero-emission alternative that offers a flexible, energy-efficient, and environmentally friendly option for last-mile logistics while ensuring product safety in the final stage of delivery.